2010
DOI: 10.2174/157341210791202636
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Separation of Pharmaceuticals by High Performance Liquid Chromatography

Abstract: The increasing demand for enantiopure drugs has led to the development of a variety of stereoselective separation technologies. Among them, high performance liquid chromatography (HPLC) is well recognized as a powerful, fast and efficient technique, which has been successfully employed for analysis and preparation of enantiomers of drugs. Nowadays, liquid chromatographic techniques are the focus of intensive research, which lead to the rational design and production of highly selective and efficient chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 161 publications
(163 reference statements)
0
24
0
1
Order By: Relevance
“…Thus, an efficient and economic method is necessary to be developed for precise determination of enantiomeric excess (e.e.%) of the thiazolidine-2-carboxylic acid enantiomers. Among the available methods for the separation of enantiomers, the HPLC method with chiral stationary phases (CSPs) is more rapid and efficient in terms of resolution [13][14][15][16]. Our experimental results indicated that thiazolidine-2-carboxylic acid can not be separated directly on the popular CSPs satisfactorily.…”
Section: Introductionmentioning
confidence: 92%
“…Thus, an efficient and economic method is necessary to be developed for precise determination of enantiomeric excess (e.e.%) of the thiazolidine-2-carboxylic acid enantiomers. Among the available methods for the separation of enantiomers, the HPLC method with chiral stationary phases (CSPs) is more rapid and efficient in terms of resolution [13][14][15][16]. Our experimental results indicated that thiazolidine-2-carboxylic acid can not be separated directly on the popular CSPs satisfactorily.…”
Section: Introductionmentioning
confidence: 92%
“…Among the methods used for the chiral resolution, enantio separation by HPLC using CSPs is currently the most popular one. [7][8][9][10][11][12] For this reason, significant effort was devoted to the development of new effective CSPs in recent years. For this purpose, various kinds of CSPs have been developed and tested so far.…”
Section: Introductionmentioning
confidence: 99%
“…Although many chiral compounds can be separated by HPLC effectively [13,14], the absolute configurations of the isomers cannot be confirmed directly [15]. e.g.…”
Section: Introductionmentioning
confidence: 99%